Modeling of LCA-chain segment for Biofuels as an instrument for the protection of the population - Baťa Robert (WSEAS Press, 2013)
The sustainably development is connected with information needs. The development of biofuels and renewable energy sources utilization requires a lot of analysis, to be implemented well. The countries that support these activities must often deal with problems arising both from the often high prices of energy and from criticism of various kinds of arguments from high environmental burden induced by these sources to the topics focused on their inefficiency. However, these problems are caused by lack of information in the implementation of policy decisions. A clear answer as to what resources should be given priority or how to compile ranking of priorities and to what the arguments are true, can be given by the most accurate mapping of these processes. This article focuses on a possible sample procedure.
Modelování části řetězce LCA biopaliv jako nástroj pro ochranu obyvatelstva.
Keywords: biofuels; decision making support; energy and material flows; environmental burden; modeling; petri nets; sustainable development; biopaliva; podpopra rozhodovacích procesů; energetické a látkové toky; zátěž životního prostředí; modelování; Petriho sítě; udržitelný rozvoj